2008
DOI: 10.1128/ec.00048-07
|View full text |Cite
|
Sign up to set email alerts
|

Bot1p Is Required for Mitochondrial Translation, Respiratory Function, and Normal Cell Morphology in the Fission Yeast Schizosaccharomyces pombe

Abstract: Maintenance of cell morphology is essential for normal cell function. For eukaryotic cells, a growing body of recent evidence highlights a close interdependence between mitochondrial function, the cytoskeleton, and cell cycle control mechanisms; however, the molecular details of this interconnection are still not completely understood. We have identified a novel protein, Bot1p, in the fission yeast Schizosaccharomyces pombe. Mitochondria are energy-generating organelles that participate in multiple cell signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Bot1 and Tim54 were found to be involved in cell wall maintenance, supported by the increased sensitivity to SDS in the heterozygous strains carrying bot1 and tim54 mutations. A similar function in cell wall maintenance has been reported for S. pombe Bot1 ( 59 ). The C. neoformans protein Saf2 is also involved in the cell wall regulatory network, as suggested by the sensitivity of the saf2 Δ mutant to SDS.…”
Section: Discussionsupporting
confidence: 81%
“…Bot1 and Tim54 were found to be involved in cell wall maintenance, supported by the increased sensitivity to SDS in the heterozygous strains carrying bot1 and tim54 mutations. A similar function in cell wall maintenance has been reported for S. pombe Bot1 ( 59 ). The C. neoformans protein Saf2 is also involved in the cell wall regulatory network, as suggested by the sensitivity of the saf2 Δ mutant to SDS.…”
Section: Discussionsupporting
confidence: 81%
“…For unknown reasons, in vivo labeling of mitochondrial proteins in S. pombe is much less efficient than in S. cerevisiae and human and requires a relatively long time ( 41 , 56 ). Nevertheless, the approach used here has been successfully used in S. pombe ( 41 , 61 , 65 ). Using this approach, we could identify all proteins synthesized by mitochondria based on their sizes and published results ( 41 , 61 , 65 ).…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the approach used here has been successfully used in S. pombe ( 41 , 61 , 65 ). Using this approach, we could identify all proteins synthesized by mitochondria based on their sizes and published results ( 41 , 61 , 65 ). As shown in Figure 3A , the levels of mtDNA-encoded proteins were substantially decreased in Δ ppr10 cells compared to WT cells, indicating that ppr10 is required for the synthesis of mtDNA-encoded proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in fission yeast have identified orb mutants that are spherical because cells fail to grow in a polarized manner, ban (banana) mutants that have a curved or bent cell phenotype because cells no longer orientate the growth zones at 180° along the long axis of the cell, and tea (tip elongation aberrant) mutants, which form a new growth zone in the wrong place often at 90° to the long axis of the cell [ 2 , 3 ]. Other cell shape mutants included bottle- or skittle-shaped cells and more generally misshapen cells [ 37 ]. We screened the deletion mutants for shape defects using the following seven categories to describe the mutant phenotypes (see figure 1 and electronic supplementary material 1, table S5 d–f , j–l , n for gene lists).…”
Section: Resultsmentioning
confidence: 99%